Dataset on the physical characterization of biopolymer coated magnetic nanoparticles - Bano, Shazia (Data Brief, 2016)
The data presented in this article is related to the research article entitled “Paclitaxel loaded magnetic nanocomposites with folate modified chitosan/carboxymethyl surface; a vehicle for imaging and targeted drug delivery” (S. Bano, M. Afzal, M.M. Waraich, K. Alamgir, S. Nazir, 2016) [1]. It contains the absorbance spectra, band gap energies of pure nickel-ferrite nano cores (NFs), and calibration curve of Paclitaxel. Thermal stability analysis of pure NFs, chitosan (CS) and carboxymethyl cellulose (CMC)-conjugated NFs samples is also included in the data.